Paraguay : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2009)
After five years of Paraguay's high growth led, in part by agro-exporting sectors, the external environment has turned less favorable, with a sharp decline of export prices and a curtailment of external credit lines. The Selected Issues paper for Paraguay discusses economic development and policies. Over the same period, inflation remained above 5 percent, but hovered around 10 percent in the last two years, fed in part by supply shocks but possibly also by an overheating of the economy.